J.-K. Huysmans : un monologue qui n’en finit pas - Sadkowska-Fidala, Agata (Verbum – Analecta Neolatina, 2010)
In Huysmans’ novels, one may notice that evolution of the composition leads to the rejection of the traditional model of writing. The novel’s action gradually disappears and consequently the dialogues are being transformed into internal monologues. The exchange of artificial and didactic ideas between the characters is used to replace the traditional conversation. The aim is to create the world in which the authors’ fascinations are transmitted from one character to another reflecting the whole complexity of Huysmans adoration for art, literature, food, etc. These monodialogues become a space where the author and its work unites to form a new quality of art.